2022
DOI: 10.1002/jmv.28031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and illness course based on pathogen among children with respiratory illness presenting to an emergency department

Abstract: Upper respiratory illnesses due to viruses are the most common reason for pediatric emergency department (ED) visits in the United States. We explored the clinical characteristics, hospitalization risk, and symptom duration of children in an ED setting by respiratory pathogen including coinfections. A retrospective analysis was conducted from a randomized controlled trial evaluating a rapid molecular pathogen panel among 931 children 1 month to 18 years of age with acute respiratory illness.We assessed hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Severe outcomes such as hospitalization and mortality in cases of infection are predominantly associated with viral respiratory infections. Notably, respiratory syncytial virus (RSV), human rhinovirus (HRV), and human metapneumovirus (HMPV) are significant pathogens responsible for acute respiratory infections across all age groups globally [ 4 , 5 ]. RSV, first isolated from children in 1957, is considered the most critical virus causing acute respiratory infections in children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe outcomes such as hospitalization and mortality in cases of infection are predominantly associated with viral respiratory infections. Notably, respiratory syncytial virus (RSV), human rhinovirus (HRV), and human metapneumovirus (HMPV) are significant pathogens responsible for acute respiratory infections across all age groups globally [ 4 , 5 ]. RSV, first isolated from children in 1957, is considered the most critical virus causing acute respiratory infections in children [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Studies evaluating clinical outcomes for children positive for HRV/ENT on RM-PCR testing remain limited, with analyses focusing on inpatient or clinical outcomes in specific populations. [13][14][15][16][17] A 2014 analysis of inpatient clinical measures demonstrated that children with HRV/ENT positivity on RM-PCR were likelier to be hospitalized and have more severe illnesses than those positive for other viruses. 18 An outpatient analysis evaluating the clinical and socioeconomic burden of HRV/ ENT positivity in adults and children revealed that under-17-yearolds positive for HRV/ENT on RM-PCR were likelier than adults to seek medical care.…”
mentioning
confidence: 99%